The challenges of the Private Sector Driven Veterinary Extension Services Delivery in the Dairy Sector in Uganda - Mbowa, Swaibu; Shinyekwa, Isaac; Mayanja Lwanga, Musa (Economic Policy Research Centre (EPRC), 2012)
The privatization of veterinary extension services delivery in Uganda opened more opportunities for the private sector in the provision of extension services and supply of essential inputs demanded by a growing and more dynamic dairy sector. Consequently, the number of agents profoundly increased – and the markets became flooded with new and untested inputs (from the unregulated private sector). One big setback emerging – relates to the growing efficacy doubts and negative experiences (including losing money or animals) associated with use of inputs on the market, contributing to non-adoption of essential inputs. Selective adoption of essential inputs in dairy farming is also wide spread. The way forward requires impartation of proper and recommended skills in livestock husbandry practices. This will entail building new information dissemination networks by strengthening the capacity to channel veterinary extension support services via farmer groups centred information delivery institutions (co-operatives) - where dairy farmers can easily pick demonstrated evidence on the efficacy of the inputs available on the market from trusted fellow farmers.